Effects of Lean, Agile and Resilient Supply Chain on Retail Performance –The Case of Food Sector in Saudi Arabia - Alharbi, Abdullah (Curtin University, 2022)
This study investigates the effect of an integrated supply chain combining the leanness, resilience, and agility elements in food retail industry of Saudi Arabia. Using a mixed method approach the findings suggest that the integrated supply chain enhances retail performance significantly. In particular the role of resilience came out to be extremely vital. The findings will help food retail managers of Saudi Arabia to manage their supply chain effectively in achieving retail success.